Hubungan antara Intimate Friendship dengan Self Disclosure pada Siswa Kelas XI SMA N 4 Kota Padang Pengguna Media Sosial Instagram - Sherly Febriani; Ifani Candra; Krisnova Nastasia (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
The aim of this research is to see whether there is a relationship between intimate friendship and selfdisclosure in class XI students of SMA N 4 Padang City , Instagram social media users . The dependent variable in this study is Self Disclosure and the independent variable is Intimate Friendship . Measuring instrument used in this study was largely skal a Intimate Friendship and Scale Self Disclosure . The sampling technique in this study is probability sampling, namely, a sampling technique that provides equal opportunities for each element (member) of the population to be selected as a sample member. The probability sampling technique used is simple random sampling. The sample in this study were 147 students of class XI SMA N 4 Padang City . The test results show the coefficient of validity on Intimate Friendship moves from 0, 433 to 0.819, while the coefficient of reliability is 0, 962, And the coefficient of validity on Self Disclosure move from 0,327 to 0,839 while the coefficient of reliability is 0,926. Based on data analysis, correlation values of 0, 165 with a level of signifi Kansi 0,046 which means that the hypothesis is accepted. This shows that there is a significant relationship between Intimate Friendship and Self Disclosure in class XI SMA N 4 Padang City Social Media Users Instagram . With the effective contribution of Intimate Friendship with Self Disclosure to class XI students of SMA N 4 Padang City, Social Media Users Instagram 3 %.